Impregnasi dengan Asap Cair Terhadap Kualitas Ribbed Smoked Sheet di PT. Perkebunan Nusantara III Dolok Merawan - Dede Ibrahim Muthawali (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. Of the experiments that have been done, adding liquid smoke in a sheet used 4,7 ml, 4,95 ml, and 5,2 ml in which the sheet  resulting brownish yellow with category RSS I and RSS II. Sheet produced on RSS Classification of I that with the addition of 4,95 ml of liquid smoke on the concentration of 10%, the concentration of the most ideal where there is no presence of popcorn or bubble on the sheet. Whereas at a concentration of 5% by volume of liquid smoke with 5,2 ml have results at a temperature of 50-600C are RSS I will but at temperatures above 600C changes on sheet to RSS II it is because the temperature is too hot so that the sheet obtained broken with the bubbles. Keyword: liquid smoke, sheet, brownish yellow, bubbl